Partisipasi Masyarakat Dalam Pengembangan Desa Wisata Edukasi: Studi di Desa Wisata Sumberbulu Kecamatan Mojogedang Kabupaten Karanganyar - Junitaningsih, Fadila; Pramono, Joko; Winduro, Wirid (Solidaritas, 2024)
One of the growing tourism trends is tourism villages. The beginning of Sumberbulu Tourism Village, Mojogedang District, Karanganyar Regency, was formed from the existence of tourism opportunities to make Sumberbulu Tourism Village included in the top 50 of the 2021 Indonesian Tourism Village Award (ADWI) and won 1st place in the souvenir category. Welcomed by high community participation is the basis for building cooperation in tourism development. Based on the title presented above, the problem in this research is the form of community participation in the development of Sumberbulu Tourism Village. The method used in this research is descriptive qualitative using indicators put forward by Josef Riwu Kaho (2007: 127) namely participation in decision making, participation in implementation, participation in benefit taking and participation in evaluation. This research uses a qualitative research approach with a qualitative analysis model using the Miles, Huberman and Saldana model, namely by (1) Data Collection, (2) Data Condensation, (3) Data Presentation and (4) Conclusion Drawing. The data collection techniques used are observation, interviews and documentation. The results showed that community participation in the development of Sumberbulu Tourism Village, Mojogedang District, Karanganyar Regency was considered very good. This can be seen from the active participation of the community in the development of tourist villages, starting from the community participating in making the stages of planning, participating in implementing development activities through organized trainings, taking advantage of the development of tourist villages in the form of increased economic welfare and program evaluation activities that have been implemented. Keywords: Community Participation, Tourism Village.